2021
DOI: 10.1016/j.annonc.2021.08.2049
|View full text |Cite
|
Sign up to set email alerts
|

53P Expression of sodium-dependent phosphate transporter NaPi2b is downregulated in malignant ovarian tumors after neoadjuvant chemotherapy

Abstract: Background: SARS-CoV-2 Virus can trigger severe pneumonia and lead to acute respiratory distress syndrome. Data from clinical, in vitro, and in vivo suggest that virusinduced cytokine dysregulation is a contributory factor to the pathogenesis. Drugs targeting the same are being tried.Methods: To obtain a better understanding of the molecular events, we studied the transcriptome of infected macrophages and obtained a list of incriminated pathways using Gene Set Enrichment Analysis. Co-expression gene analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study of Blackburn et al showed encouraging results in a murine model of chronic viral infection. It was proved that the dual blockade of LAG-3 and PD-1 in vivo resulted in significant increases in antigen-specific CD8+ T cell numbers and function, as well as marked reductions in viral titer [ 128 ]. The combination of anti-PD-1 and anti-LAG-3 therapy may be beneficial in Hodgkin lymphoma (HL).…”
Section: Anti-lag-3 Antibody-based Therapiesmentioning
confidence: 99%
“…The study of Blackburn et al showed encouraging results in a murine model of chronic viral infection. It was proved that the dual blockade of LAG-3 and PD-1 in vivo resulted in significant increases in antigen-specific CD8+ T cell numbers and function, as well as marked reductions in viral titer [ 128 ]. The combination of anti-PD-1 and anti-LAG-3 therapy may be beneficial in Hodgkin lymphoma (HL).…”
Section: Anti-lag-3 Antibody-based Therapiesmentioning
confidence: 99%